Strategic analysis of petty corruption with an intermediary - Ariane Lambert-Mogiliansky; Mukul Majumdar; Roy Radner (Cornell University, Center for Analytical Economics (CAE), 2008)
This note reports part of a larger study of petty corruption by government bureaucrats in the process of approving new business projects. Each bureaucrat may demand a bribe as a condition of approval. Entrepreneurs use the services of an intermediary who, for a fee, undertakes to obtain all of the required approvals. In a dynamic game model we investigate (1) the multiplicity of equilibria, (2) the equilibria that are socially efficient, and (3) the equilibria that maximize the total expected bureaucrats' bribe income. We compare these results with those for the case in which entrepreneurs apply directly to the bureaucrats.
Keywords: 330; Korruption; Dynamisches Spiel; Unternehmensgründung; Unternehmensdienstleistung; Theorie